MECHANISMS FOR FORMING THE REGION’S BALANCED DEVELOPMENT STRATEGY IN THE CONDITIONS OF THE DIGITAL ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: this article discusses the imbalances in the development of regional systems in the context of the digital economy. The development of mechanisms and tools for the formation of a balanced socio-economic development strategy of the region is an urgent scientific task. Using a systematic approach, an enlarged diagram of the mechanism for the formation of a balanced development strategy of the region is developed and proposed. The sources of the formation of imbalances, priorities for the socio-economic development of the region, possible levers and tools for ensuring balanced development, and directions for the formation of scenarios and strategic alternatives for the balanced socio-economic development of the regions are developed.